Validity and Reliability of Persian Version of Student Attitude Scale Toward Physical Education (SATPES)) - Meysam Biyabani; Rasool Hemayat talab; Fazlollah Bagher zadeh; Elaheh Arab ameri (University of Tehran, 2019)
Attitude plays an important role in success and is one of the aspects thataffect students' learning. The aim of the present study was to investigate thevalidity and reliability of Persian version of Student's Attitude TowardPhysical Education Scale (SATPES). This study was descriptive-correlationand the statistical population consisted of all 12-14-year-old students of 1stgrade of middle schools in Tehran city. Student's Attitude Toward PhysicalEducation Scale (SATPES) was used in this study and Subramaniam andSilverman (2000) had validated it. It included two subscales and 20 itemswith 5-point Likert responses and 415 questionnaires of this scale werecompleted by students. Test-retest method was applied in order to calculatethe temporal reliability and Cronbach's alpha was used to determine internalconsistency. To determine construct validity, confirmatory and exploratoryfactor analyses were applied. The results showed that Persian version ofSATPES supported two dimensional approach of attitude in enjoyment andbenefit with 20 items; thus validity (fit indexes were above the acceptablelevel of 0.9) and reliability (above the acceptable level of 0.7) of the scalewere confirmed. In conclusion, Persian version of Student's Attitude TowardPhysical Education Scale is recommended to measure students' attitude